Kualitas Laporan Keuangan Desa: Sebuah Studi Di Kabupaten Boyolali - Junaidi Junaidi; Briyan Efflin Syahputra; Enny Itje Sela; Mohamad Mahsun (Jurnal Reviu Akuntansi dan Keuangan, 2024)
Purpose: This study examines how financial management and asset management affect the quality of village financial reports in Boyolali Regency, Central Java. Methodology/approach: In order to gather research data, surveys and questionnaires were employed as the primary method and instruments in this quantitatively oriented study. This study also employed the FGD method to generate the question items/indicators included in the questionnaire. 252 village administrations from the Boyolali Regency participated in this study as respondents. Moreover, survey data was analyzed using multiple regression analysis. Findings: The quality of village financial reports has been demonstrated to be positively impacted by both asset and financial management. Practical implications: The findings of this study can serve as a valuable foundation and point of reference for regional administrations and associated parties, particularly for village administrations across Indonesia, so they can create high-quality village financial reports. Originality/value: The research model used in this study is still relatively rare in Indonesia. This study has simultaneously analyzed the influence of financial management and asset management factors in order to improve the quality of village financial reporting.